O ensino de Ciências por investigação no 6º Ano: o conceito de pressão do ar - França, Nadynne Nara Amaral de (2019)
Among the various proposals presented in the National Curriculum Parameters (PCN) of Sciences is to train citizens capable of questioning reality. This can occur by formulating problems and using strategy for their proper resolution. Such strategies provide the subject with the stimulation of logical thinking, creativity, intuition and the capacity for critical analysis. Physics, being one of the sciences that help explain natural phenomena, is only inserted in the students' school life in the last year of Elementary School II (9th grade). It is only outlined, without much concern for an effective introduction that makes learning this subject meaningful. Teaching physical content in elementary school is extremely important. At this stage learners are motivated to discover something new, which implies a better understanding of what happens in the world in which they are inserted. For this reason, it is believed that physics, when still inserted in elementary school, has great chances to help promote a democratization in science teaching, so essential for the future life of students. This insertion of Physics in Elementary School can be done through investigative activities organized in an Investigative Teaching Sequence (SEI). In the case of this work, we used an SEI applied to students of the 6th grade of a school of the State Network of Alagoas in the city of Maceió. Between July and August 2017, 4 experiments were carried out, assembled with low cost materials, whose objective was to encourage students to build the concept of Atmospheric Pressure. This research was qualitative with participant research approach, with data analyzed according to content analysis and obtained through questionnaires applied to the classes and the teacher. As a result, it was observed that experimentation as an investigative activity can help students build knowledge, as well as providing a way out of their comfort zone to search for their own problem solving.